AN EVALUATION OF SUPPLEMENTAL AND ROUTINE IMMUNIZATION COVERAGE IN MAIDUGURI METROPOLIS, BORNO STATE, NIGEIRA - BASSI AP; AMBE JP; MANGORO ZM (Ntec Specialist, 2008)
Background: Nigeria is currently the main focus of the polio eradication initiative. Strong routine immunization coverage offers better sustained protection to the most vulnerable age group (0-59 months). Maiduguri is the commercial nerve centre and the seat of government of Borno state. Objective: To evaluate supplemental and routine immunization coverage in Maiduguri, Borno State. Methods: This is a thirty-by-seven cluster survey conducted to assess the status of immunization in the metropolis. The WHO standardized EPI questionnaire was used to allow for comparison with other nations. A total of two hundred and ten mothers were interviewed from thirty clusters. Result: The responses revealed a coverage of 78.8 percent for Ihe April 2004 NIDs amongst children 0-59 months of age. Routine immunization coverage for children 12-23 months of age were BCG 45%, DPT-324%, and Measles 20% respectively. The BCG to measles and DPT-1 to DPT-3 dropout rates were 44.6% and 44.1% respectively which is extremely high. Only 20% of the targeted children completed the immunization schedule. Reasons for immunization failure include lack of information by health staff on next dates 51.4%, distance from immunization centre 14.6%, unaware of the need to complete immunization schedule to afford protection for their children 15.9% and other associated reasons 18.1%. Conclusion: The quality of ongoing supplemental immunization is improving, although routine immunization coverage is below the national average of 80%. The metropolitan council and National Programme on Immunization should target caregivers and religious leaders at all levels of the metropolis by both traditional and the electronic media on the importance of completing immunization shedules